1984
DOI: 10.1111/j.1476-5381.1984.tb10101.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic transmission in the dog mesenteric vein and its modulation by α‐adrenoceptor antagonists

Abstract: Adrenergic transmission was investigated in the dog mesenteric vein by recording electrical responses of single smooth muscle cells to perivascular nerve stimulation. Perivascular nerve stimulation generated an excitatory junction potential (e.j.p.) and a slow depolarization of the membrane. The amplitude of the e.j.p. was increased by increasing the stimulus intensity, and at high intensity, a spike potential was generated. Repetitive stimulation of the nerves showed facilitation of e.j.ps and enhanced the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

1985
1985
1989
1989

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
4
21
1
Order By: Relevance
“…Thus, on the basis of growing evidence demonstrating the presence ofa2-adrenoceptors in venous smooth muscle (Makita, 1983;Suzuki, 1984;Cheung, 1985;Docherty & Hyland, 1985), it is reasonable to assume that the results obtained in the present study indicate that both a,-and M2-adrenoceptors are present in the arterial circulation of the cat hindquarters, while there was an exclusive, or at least predominant, X2-adrenoceptor population in the venous circulation. These findings are consistent with others (De Mey & Vanhoutte, 1981; Vanhoutte, 1982;Glusa & Markwardt, 1983) which indicate that venous smooth muscle contains a greater proportion of o2-adrenoceptors than does arterial smooth muscle, although all previous evidence was based on in vitro data.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, on the basis of growing evidence demonstrating the presence ofa2-adrenoceptors in venous smooth muscle (Makita, 1983;Suzuki, 1984;Cheung, 1985;Docherty & Hyland, 1985), it is reasonable to assume that the results obtained in the present study indicate that both a,-and M2-adrenoceptors are present in the arterial circulation of the cat hindquarters, while there was an exclusive, or at least predominant, X2-adrenoceptor population in the venous circulation. These findings are consistent with others (De Mey & Vanhoutte, 1981; Vanhoutte, 1982;Glusa & Markwardt, 1983) which indicate that venous smooth muscle contains a greater proportion of o2-adrenoceptors than does arterial smooth muscle, although all previous evidence was based on in vitro data.…”
Section: Discussionsupporting
confidence: 54%
“…with the slow depolarization which may be generated by NA, the ej.p. could be used as an indicator of the amount of NA released during perivascular nerve stimulation (Suzuki, 1984;Suzuki et al, 1984). The present experiments demonstrated that in the rabbit saphenous artery ACh inhibited the amplitude of the ej.p., as has been demonstrated in the guinea-pig mesenteric artery (Kuriyama & Suzuki, 1981).…”
Section: Ach-induced Hyperpolarization Ofsmooth Muscle Membranementioning
confidence: 73%
“…amplitude and depresses the facilitation process of e.j.ps in the guinea-pig mesenteric artery (Kuriyama & Makita, 1983). However, in the rabbit saphenous or ear arteries (Holman & Surprenant, 1980) and in the dog mesenteric vein (Suzuki, 1984), the decrease in e.j.p. amplitude during NA application is not prevented by ca-adrenoceptor antagonists which possess higher selectivity for the CX2-subtype.…”
Section: Discussionmentioning
confidence: 90%